Analisis Perbandingan Peraturan Pemerintah Nomor 23 Tahun 2018 dan Pajak Penghasilan Pasal 25 untuk Efisiensi Beban Pajak UMKM (Studi Kasus pada CV Jifast, CV Rizqi Utama, Hayu Jalan Creative Tour) - Nurul Laila Dewi; Yeti Apriliawati (Indonesian Accounting Literacy Journal, 2021)
This study aims to efficiency the tax burden of MSMEs by comparing two income tax calculation mechanisms, namely Government Regulation Number 23 of 2018 and Income Tax Article 25 and to determine the readiness of MSMEs to switch to Income Tax Article 25 after the grace period of Government Regulation Number 23 of 2018 ends. This type of research is descriptive quantitative where the researcher will calculate the tax burden of MSMEs and make an analysis based on the data collected by the triangulation method. The results of calculating the tax burden of the two tax mechanisms are compared to determine which tax calculation mechanism produces the smallest tax burden. A tax plan is made for MSMEs which are the research subjects so that they can be applied in the future. This research is expected to be a reference for the application of Corporate Income Tax and Government Regulation Number 23 of 2018 by other MSMEs which are included in the same Business Field Classification as the subject of this research MSMEs.